Olivia C. Harrison. Natives Against Nativism: Antiracism and Indigenous Critique in Postcolonial France. University of Minnesota Press, 2023. - André Pettman (Studies in 20th & 21st Century Literature, 2024)
Review of Olivia C. Harrison. Natives against Nativism: Antiracism and Indigenous Critique in Postcolonial France. University of Minnesota Press, 2023. 296 pp.
Keywords: Indigeneity; Postcolonial Studies; French and Francophone Studies; Palestine; American Indian; Antiracism; Migrant Rights